Just one thing developing a Buddha brain one simple practice at a time - Hanson, Rick. (Oakland, CA : New Harbinger Publications, 2011)
"This book offers simple brain-training practices you can do every day to protect against stress, lift your mood, and find greater emotional resilience."--P. [4] of cover.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Meditation -- Buddhism; Buddhism and science; Happiness; Wisdom; RELIGION / Buddhism / General; Electronic books